2021
DOI: 10.3390/ijms22115878
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer: Targeting of Steroid Hormones in Cancerogenesis and Diagnostics

Abstract: Breast cancer is the most common malignancy in women with high mortality. Sensitive and specific methods for the detection, characterization and quantification of endogenous steroids in body fluids or tissues are needed for the diagnosis, treatment and prognosis of breast cancer and many other diseases. At present, non-invasive diagnostic methods are gaining more and more prominence, which enable a relatively fast and painless way of detecting many diseases. Metabolomics is a promising analytical method, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 97 publications
(104 reference statements)
1
10
0
1
Order By: Relevance
“…Nevertheless, in the long-term use, the preventive effects of aspirin on BC may be attributed to the other pathways [ 24 , 26 , 35 ], and they are probably more important than their effects on estrogen levels. Second, given that estrogen levels were significantly higher in BC tissue than in plasma and that local estrogen production plays an essential role in the proliferation of invasive breast cancer cells in postmenopausal women [ 19 ], in the long term, locally chemopreventive effects of aspirin on breast tissue [ 30 ] may be more important than those on circulating levels [ 11 ]. Third, the importance of measuring estrogen metabolites in BC has received less attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, in the long-term use, the preventive effects of aspirin on BC may be attributed to the other pathways [ 24 , 26 , 35 ], and they are probably more important than their effects on estrogen levels. Second, given that estrogen levels were significantly higher in BC tissue than in plasma and that local estrogen production plays an essential role in the proliferation of invasive breast cancer cells in postmenopausal women [ 19 ], in the long term, locally chemopreventive effects of aspirin on breast tissue [ 30 ] may be more important than those on circulating levels [ 11 ]. Third, the importance of measuring estrogen metabolites in BC has received less attention.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, a dose-response meta-analysis [ 16 ] of cohort studies from approximately 1 million people concluded that the optimal aspirin dose for the chemoprevention of BC might be in the range of < 325 mg per day, 2–7 times/week, accompanied by long-term administration (> 5 years). Given the chemopreventive effects of aspirin in BC [ 17 , 18 ] and the relations between high serum levels of steroids (estrogens and androgens) and increased BC risk in postmenopausal women [ 19 – 21 ], some studies were deliberated on introducing aspirin dosing to lower estrogen levels. However, these studies [ 17 , 22 , 23 ] and a randomized clinical trial (RCT) [ 11 ] did not succeed in concluding that the dose, frequency, and duration of aspirin use observed in the prevention of BC necessarily complied with those of estrogen lowering.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the available publications indicate both stimulatory and inhibitory actions of elderberry extract and its constituents rutin, anthocyanins and lectins on regulators of embryogenesis, embryonal cancerogenesis and steroidogenesis. The ability of steroid hormones to promote both embryo development [108] and malignant transformation [109] is well-known. Therefore, the influence of elderberry molecules' action on embryo and cancerogenesis through the estrogen/estrogen receptor system could be proposed.…”
Section: Effect Of Elderberry and Its Constituents On Embryomentioning
confidence: 99%
“…These observations suggest that steroid hormones could be one of the mediators of the black elderberry and its molecule rutin on ovarian functions, and so can promote ovarian cell viability through the stimulation of steroidogenesis [98]. Finally, the influence of elderberry extract on embryonal cancer cell estrogen/estrogen receptor systems [57], as well as the importance of this system in control of embryogenesis [108] and cancerogenesis [109], indicate that elderberry can affect embryos via estrogens and its receptors. Nevertheless, such hypotheses require direct experimental confirmation.…”
Section: Extracellular Mechanisms Of Action Of Elderberry and Its Con...mentioning
confidence: 99%
“…The morbidity and mortality of different molecular subtypes of BC differ (6). Distinct subtypes of BC are usually treated with different ways in clinical management (7). Drug therapy can be roughly divided into endocrine therapy, chemotherapy, targeted therapy, and immunotherapy (8).…”
Section: Introductionmentioning
confidence: 99%